Soil structure interaction effects observed in the in situ forced vibration and pushover tests of school buildings in Taiwan and their modeling considering the foundation flexibility. - Ko, Yung-Yen
In the conventional structural seismic analysis, the rigid base model is usually adopted without considering the flexibility of the ground, leading to inaccurate estimation of the vibration characteristics and the seismic response of the structure. In 2007, several in situ tests were conducted by the National Center for Research on Earthquake Engineering (NCREE) on the school buildings in the Guanmiao Elementary School in Tainan, Taiwan. For the study of soil?structure interaction (SSI) effects, the forced vibration test (FVT) was performed, and the deformation of the foundation system was measured during the pushover test. In this paper, the results of these in situ tests are presented and discussed, and the finite element models of the school buildings were generated for the simulation of the FVT and for the pushover analysis in order to investigate the difference between the rigid base model and the flexible base model. Results show that the mechanical properties of the structure and the foundation could be demonstrated in these in situ tests. Additionally, the introduction of the flexibility of the foundation has a considerable influence on the results of structural analysis.
Keywords: School building; Pushover test; Forced vibration test; SSI effect; FE analysis